Efektivitas Pijat dengan Teknik Effleurage terhadap Tingkat Sensitivitas Kaki pada Pasien Diabetes Melitus Tipe 2 - Anisa Fitriyani; Yoany Maria Vianney Bita Aty; Dominggos Gonsalves; Trifonia Sri Nurwela; Aben B.Y.H.Romana (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Peripheral neuropathy is a common chronic complication among patients with type 2 diabetes mellitus (DM) and contributes to decreased foot sensitivity, increasing the risk of foot ulcers and lower-limb amputation. Prevention of this complication requires effective, safe, and feasible nonpharmacological interventions in primary healthcare settings. One intervention with potential benefits is massage using the effleurage technique. This study aimed to analyze the effect of effleurage massage on foot sensitivity among patients with type 2 DM at Sikumana Primary Health Center, Kupang City. This study employed a quasi-experimental design with a non-equivalent control group approach. A total of 34 respondents were divided into an intervention group and a control group, each consisting of 17 participants selected through purposive sampling. Foot sensitivity was assessed using the 10 g Semmes–Weinstein Monofilament Test before and after the intervention. The intervention group received effleurage massage on both feet twice a week for two weeks, while the control group received standard care. Data were analyzed using the Wilcoxon and Mann–Whitney tests. The findings showed a significant improvement in foot sensitivity in the intervention group (Z = −3.500; p < 0.05), whereas the control group showed no significant change (Z = −1.000; p > 0.05). Posttest analysis also revealed a significant difference between groups (Z = −4.128; p < 0.05). In conclusion, effleurage massage effectively improves foot sensitivity and can be recommended as a complementary nursing intervention to prevent diabetic neuropathy.